Relation of Dietary Habits and Weaning with Nutritional Status of Children - Enda Silvia Putri; Siti Maisyaroh Fitri Siregar; Arfah Husna; Marniati Marniati; Darmawan Darmawan (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2020)
Background of the problems that occurred at the Mereubo Health Center of 114 toddlers in Peunaga Cut Ujong Village there were 3 under five malnourished toddlers, 111 under five with good nutrition status, and in Meureubo village there were 2 under five underfives and 139 underfives with good nutrition status. The purpose research was looked relation of dietary habbits and weaning with nutritional status of children. The research method is analytic survey with cross sectional survey design. The population in this study were all children aged 9-59 months in Peunaga Cut Ujong Village and Meureubo Village, Meureubo District, West Aceh Regency with 255 toddlers, and use formula solvin the sample was 72 toddlers with technic sample was simple random sampling, and analysis used chi-square-test . The results showed an association of dietary habbits (P.Value 0.015 <0.05 and OR value = 0.067), as well as the relationship of weaning (P.Value 0,000 <0.05 and OR value = 17.0) with the nutritional status of children under five in the Village Peunaga Cut Ujong, then there is a relationship between dietary habbits (P.Value 0.011 <0.05 and OR value = 0.135) and the relationship between weaning (P.Value 0.001 <0.05 and OR value = 16.7) with the nutritional status of children in Meureubo Village. The research conclusion was relationship weaning  was stronger than dietary habbits with  nutrional status. The suggestions to the puskesmas provide understanding to mothers about the importance of eating patterns and provide exclusive breastfeeding and breastfeeding for two to toddlers, so that toddlers obtain nutritional status and growth development properly.